Grapevine canopy management effects on Merlot wine composition - Miele, Alberto; Rizzon, Luiz Antenor; Mandelli, Francisco (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to evaluate the effect of grapevine (Vitis vinifera L.) summer pruning on Merlot wine composition. An experiment was carried out from 1993/1994 to 1996/1997 in Bento Gonçalves, RS, Brazil, using a control and 11 summer pruning in grapevines trained in pergola system. Principal component analysis showed that the summer pruning effects varied by year. Considering the average of the four years, the first three principal components were responsible for 72% of the total variation. Sprouting, topping, and removal of all leaves below grapevine clusters at the beginning of bloom had high values of color intensity, absorbances at 280 and 520 nm, anthocyanins, tannins, alcohol, 3-methyl-1-butanol/2-methyl-1-propanol, alcohol in weight/reduced dry extract, and phosphorus and was the best alternative for the production of quality Merlot wine.
Keywords: Vitis vinifera; summer pruning; sprouting; topping; leaf removal